2017
DOI: 10.18632/oncotarget.21726
|View full text |Cite
|
Sign up to set email alerts
|

The M6A methyltransferase METTL3: acting as a tumor suppressor in renal cell carcinoma

Abstract: We aimed to study the role of METTL3 in renal cell carcinoma (RCC) carcinogenesis and development. Immunohistochemistry was performed in clinical tissue microarray. Expression level of METTL3 in RCC tissues and cell lines was evaluated by quantitative real-time PCR (qRT-PCR) and western blot. Then, the effects of METTL3 on proliferation, migration, invasion and cell cycle were studied in RCC cells. Additionally, in vivo study was carried out in nude mice. Negative METTL3 expression was associated with larger t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
168
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(188 citation statements)
references
References 28 publications
17
168
1
Order By: Relevance
“…Also, m 6 A is predicted to have a role in renal cell carcinoma. This is also corroborated by Xiao et al [74], which reported that the m 6 A methyltransferase METTL3 acted as a tumor suppressor in renal cell carcinoma and publications in [75,76], which identified YTHDF2, an m 6 A binding protein, to be involved in renal cell carcinoma. Taken together, we found existing evidence to support 3 out of 5 predicted association diseases.…”
Section: Prioritized M 6 A-associated Diseasessupporting
confidence: 71%
“…Also, m 6 A is predicted to have a role in renal cell carcinoma. This is also corroborated by Xiao et al [74], which reported that the m 6 A methyltransferase METTL3 acted as a tumor suppressor in renal cell carcinoma and publications in [75,76], which identified YTHDF2, an m 6 A binding protein, to be involved in renal cell carcinoma. Taken together, we found existing evidence to support 3 out of 5 predicted association diseases.…”
Section: Prioritized M 6 A-associated Diseasessupporting
confidence: 71%
“…29 METTL3 acted as a tumour suppressor in renal cell carcinoma cells to regulate cell cycle arrest in G1 phase by targeting PI3K/Akt/mTOR signalling pathway. 34 In CRC, a recent research has verified that METTL3 could promote cell self-renewal, stem cell frequency and migration through an m6A-IGF2BP2-dependent mechanism. 37 However, another study showed that METTL3 could suppress colorectal cancer proliferation and migration through p38/ERK pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For example, METTL3 was identified as an essential oncogene to promote cell cycles and growth in acute myeloid leukaemia by targeting transcription factor SP1 . METTL3 acted as a tumour suppressor in renal cell carcinoma cells to regulate cell cycle arrest in G1 phase by targeting PI3K/Akt/mTOR signalling pathway …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin and colleagues showed that METTL3 promotes translation of oncogenic factors such as the epidermal growth factor receptor (EGFR) in LUAD cells through a mechanism independent of its methyltransferase activity (89). In contrast, METTL3/METTL14 downregulation was also shown to be associated with glioblastoma (GBM), hepatocellular carcinoma (HCC) and renal cell carcinoma (RCC) (92)(93)(94). Upregulation of METTL3 suppressed RCC tumor growth in xenografted mice, and higher METTL3 expression was associated with significantly better prognosis in RCC patients (94).…”
Section: A In Cancermentioning
confidence: 99%